Study of Z bosons produced in association with charm in the forward region - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2022)
Events containing a Z boson and a charm jet are studied for the first time in the forward region of proton-proton collisions. The data sample used corresponds to an integrated luminosity of 6 fb−1 collected at a center-of-mass energy of 13 TeV with the LHCb detector. In events with a Z boson and a jet, the fraction of charm jets is determined in intervals of Z-boson rapidity in the range 2.0<y(Z)<4.5. A sizable enhancement is observed in the forwardmost y(Z) interval, which could be indicative of a valencelike intrinsic-charm component in the proton wave function.
LHCb Collaboration: R. Aaij, F. Archili, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecná, B. Leverington, P. Li, H. Malygina, J. Marks, S. Neubert, M. Sarpis, M. Schmelling, D.J. Unverzagt, U. Uwer, R. Waldi, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 15.06.2022